2018
DOI: 10.3892/ijmm.2018.3380
|View full text |Cite
|
Sign up to set email alerts
|

Relaxant and vasoprotective effects of ginger extracts on porcine coronary arteries

Abstract: Ginger (Zingiber officinale Roscoe) is a popular Chinese herbal medicine, which is considered to warm the stomach and dispel cold in traditional Chinese medicine. Ginger is widely used to treat stomach disorders, and it has been reported to exhibit antithrombotic activity via the inhibition of platelet aggregation and thromboxane B2 production in vitro. Cardiovascular disease is associated with the aberrant functioning of the heart and circulatory system; the relatively narrow vessels of the circulation are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…This finding was confirmed by a previous study that showed the ability of ginger extract to reduce atherosclerotic lesions in the artery and to reverse the inflammatory cytokine expression and lipid profile induced in mice with atherosclerosis [115]. Another previous in vitro study demonstrated that ginger crude extract induced the relaxation of porcine coronary arteries in an endothelium-dependent manner [116]. Ginger extract was also vasoprotective in coronary arteries through the suppression of the cyclooxygenase pathway and nitric oxide synthase.…”
Section: Ginger In the Prevention And Treatment Of Degenerative DIsupporting
confidence: 74%
“…This finding was confirmed by a previous study that showed the ability of ginger extract to reduce atherosclerotic lesions in the artery and to reverse the inflammatory cytokine expression and lipid profile induced in mice with atherosclerosis [115]. Another previous in vitro study demonstrated that ginger crude extract induced the relaxation of porcine coronary arteries in an endothelium-dependent manner [116]. Ginger extract was also vasoprotective in coronary arteries through the suppression of the cyclooxygenase pathway and nitric oxide synthase.…”
Section: Ginger In the Prevention And Treatment Of Degenerative DIsupporting
confidence: 74%
“…Besides, ginger protected against hypertension-derived complications by decreasing platelet adenosine deaminase (ADA) activity and increasing the level of adenosine, which prevented platelet aggregation and promoted vasodilation in hypertensive rats [77]. Moreover, ginger extract exhibited vasoprotective effects on porcine coronary arteries by suppressing NO synthase and cyclooxygenase [81]. Furthermore, a cross-sectional study found that the probability of hypertension and coronary heart disease declined when a daily intake of ginger was increased [82].…”
Section: Bioactive Components and Bioactivities Of Gingermentioning
confidence: 99%
“…It has also been shown that the consumption of polyphenols limits the development of atheromatous lesions, which is considered a key mechanism in the endothelial lesions occurring in atherosclerosis (Grassi, Desideri, & Ferri, 2010). Furthermore, ginger phenolic compounds have vasodilatory properties, through increasing plasma nitric oxide concentration (Srinivasan, 2017;Wu et al, 2018). Nitric oxide can also reduce the plasma level of proinflammatory cytokines, reduce the platelet aggregation, and improve endothelium function (Puzserova & Bernatova, 2016).…”
Section: Discussionmentioning
confidence: 99%